Phase-preserved optical elevator - Luo, Yuan (2013)
The unique superiority of transformation optics devices designed from coordinate transformation is their capability of recovering both ray trajectory and optical path length in light manipulation. However, very few experiments have been done so far to verify this dual-recovery property from viewpoints of both ray trajectory and optical path length simultaneously. The experimental difficulties arise from the fact that most previous optical transformation optics devices only work at the nano-scale; the lack of intercomparison between data from both optical path length and ray trajectory measurement in these experiments obscured the fact that the ray path was subject to a subwavelength lateral shift that was otherwise not easily perceivable and, instead, was pointed out theoretically [B. Zhang et al. Phys. Rev. Lett. 104, 233903 (2010)]. Here, we use a simple macroscopic transformation optics device of phase-preserved optical elevator, which is a typical birefringent optical phenomenon that can virtually lift an optical image by a macroscopic distance, to demonstrate decisively the unique optical path length preservation property of transformation optics. The recovery of ray trajectory is first determined with no lateral shift in the reflected ray. The phase preservation is then verified with incoherent white-light interferometry without ambiguity and phase unwrapping.